Intimate but not intimate: The perils of workplace romance in fostering knowledge sabotage - Jun Qiu; Fatima Sultana; Shahid Iqbal; Arslan Ayub (PLoS ONE, 2023)
Extant research on workplace ostracism has investigated a victimization perspective to understand ostracism at the cost of examining the perpetrator-centric view of ostracism. The current study draws on the self-categorization theory and the social exchange theory to investigate the harmful effects of workplace romance in cultivating workplace ostracism from the perpetrator’s perspective to combat concerns for victim blaming. The study further proposes that workplace ostracism triggered by workplace romance provokes knowledge sabotage. Besides, the study investigates the moderating role of parochial altruism in the underlying linkages. The study utilizes a multisource, time-lagged research design to collect data from employees working in service sector organizations in Pakistan. The study analyzes 343 responses using SmartPLS (v 4.0). The findings of this study reveal that workplace romance elicits workplace ostracism, which, in turn, fosters knowledge sabotage. In addition, the study finds that parochial altruism strengthens the associations between (a) workplace romance and workplace ostracism and (b) workplace romance and knowledge sabotage, mediated by workplace ostracism such that the associations are more potent at higher levels of parochial altruism and vice versa. This is the first study that examines workplace romance as the perpetrator-centric antecedent of workplace ostracism, and parochial altruism exaggerates outgroup ostracism and knowledge sabotage.